2020
DOI: 10.1021/acs.langmuir.9b03489
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Immiscible Domain of Cholesterol in the Lipid Bilayer Membrane Promotes Early Stage Calcification by Inducing Oriented Nucleation of Hydroxyapatite

Abstract: Biomineralization is characterized by the fact that the crystallization of inorganic minerals is guided by an in vivo biological interface. However, the interfaces that direct calcification are widely debated up to date. In this paper, it was found that the two-dimensional (2D) immiscible domain of cholesterol in the lipid bilayer can induce the deposition of calcium phosphate by rapidly promoting the nucleation of the hydroxyapatite (001) plane. This promotion effect is related to the high lattice matching de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The results showed that the addition of POPC reduced the solubility of cholesterol in lipids, generated cholesterol microdomains at a lower concentration, and made the liposomes more stable by increasing the flexibility of the bilayer. [ 52,53 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the addition of POPC reduced the solubility of cholesterol in lipids, generated cholesterol microdomains at a lower concentration, and made the liposomes more stable by increasing the flexibility of the bilayer. [ 52,53 ]…”
Section: Discussionmentioning
confidence: 99%
“…Blank liposomes were prepared as previously described. [ 52,59 ] Briefly, 40 mg lipids with a certain composition of phospholipid and cholesterol (Table 1) was dissolved in chloroform in a pear‐shaped flask. The organic solvent was removed in a rotating vacuum evaporator at 60 °C, and a lipid film was formed.…”
Section: Methodsmentioning
confidence: 99%